Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/jb.00119-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of Four Magnetotactic Bacteria Reveals a Complex Set of Group-Specific Genes Implicated in Magnetosome Biomineralization and Function

Abstract: Magnetotactic bacteria (MTB) are a heterogeneous group of aquatic prokaryotes with a unique intracellular organelle, the magnetosome, which orients the cell along magnetic field lines. Magnetotaxis is a complex phenotype, which depends on the coordinate synthesis of magnetosomes and the ability to swim and orient along the direction caused by the interaction with the Earth's magnetic field. Although a number of putative magnetotaxis genes were recently identified within a conserved genomic magnetosome island (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
238
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(243 citation statements)
references
References 44 publications
(62 reference statements)
2
238
0
2
Order By: Relevance
“…To our knowledge, this is the first report of this pathway in 'Ca. Magnetobacterium' genus, which is different from all known autotrophic members in Nitrospirae as well as MTB in Proteobacteria that conduct either rTCA cycle or Calvin-Benson-Bassham pathway for CO 2 fixation (Garrity and Holt, 2001;Matsunaga et al, 2005;Williams et al, 2006;Richter et al, 2007;Levican et al, 2008;Goltsman et al, 2009;Lucker et al, 2010;Ji et al, 2014). Compared with rTCA and Calvin-Benson-Bassham, the WL pathway is biochemically simple and energetically favorable (Peretó et al, 1999), which may lead to a growth advantage of these microorganisms in oxygen-limited environments.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of this pathway in 'Ca. Magnetobacterium' genus, which is different from all known autotrophic members in Nitrospirae as well as MTB in Proteobacteria that conduct either rTCA cycle or Calvin-Benson-Bassham pathway for CO 2 fixation (Garrity and Holt, 2001;Matsunaga et al, 2005;Williams et al, 2006;Richter et al, 2007;Levican et al, 2008;Goltsman et al, 2009;Lucker et al, 2010;Ji et al, 2014). Compared with rTCA and Calvin-Benson-Bassham, the WL pathway is biochemically simple and energetically favorable (Peretó et al, 1999), which may lead to a growth advantage of these microorganisms in oxygen-limited environments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a set of approximately 152 genus-specific genes shared by the three Magnetospirillum strains, 28 group-specific genes, which occur in all four magnetotactic bacteria but exhibit no similarity or only remote similarity to the genes from non-magnetotactic organisms, were identified. This study revealed the magnetotactic bacteria-specific set of genes that are most likely to be involved in BacMP biomineralization (Richter et al 2007). …”
Section: Genome Analyses Of Magnetotactic Bacteriamentioning
confidence: 99%
“…Recent efforts directed towards genome sequencing of magnetotactic bacteria have provided genome information of several other strains. The draft sequence for the M. magnetotacticum strain MS-1 and the complete sequence for the magnetotactic coccus strain MC-1 were provided by the Joint Genome Institute ( JGI; http://www.jgi.doe.gov/tempweb/JGI_micro-bial/html/index.html), while the draft genome sequence of the M. gryphiswaldense strain MSR-1 was analysed in comparison with other magnetotactic bacterial genome sequences (Richter et al 2007). The comparative study revealed that approximately 891 genes were shared by all four magnetotactic bacteria.…”
Section: Genome Analyses Of Magnetotactic Bacteriamentioning
confidence: 99%
“…BLAST is an optimized comparative algorithm tool that aligns a query sequence (input data) against data records (subject sequences) by assigning optimal local alignments with high-scoring region to that of input data. The best "hit" or sequence that is uses to identify the query sequence is deduced using expectation/ expect (e-value) and the score of an alignment (S) (Richter et al, 2007). 16S rRNA sequencing gave a read of 1462 bp and BLAST search revealed the isolate as Micrococcus luteus (Acession no: KT339390; 8th August 2015).…”
Section: Identity Of Y_01mentioning
confidence: 99%